227k views
0 votes
Simplify your answer

Simplify your answer-example-1
User Robert Bue
by
5.0k points

2 Answers

6 votes

Answer:

x = 4

y = 3

Explanation:

y = 4x - 13

-4x + y = -13

2x + 3y = 17

-4x + y = -13 | ×1 |

2x + 3y = 17 | ×2 |

-4x + y = -13

4x + 6y = 34

___________+

7y = 21

y = 21/7

y = 3

2x + 3y = 17

2x + 3(3) = 17

2x + 9 = 17

2x = 17 - 9

2x = 8

x = 8/2

x = 4

User Mani
by
5.0k points
5 votes

Answer:
x=4\\y=3

Explanation:


y=4x-13\\2x+3y=17

Since our ''y'' is already isolated, you can simply plug ''y'' information into the second equation.


2x+3y=17\\2x+3(4x-13)=17\\2x+12x-39=17\\14x=17+39\\14x=56\\x=(56)/(14) \\x=4

Now we can use the first equation and replace ''x'' to find ''y''


y=4x-13\\y=4(4)-13\\y=16-13\\y=3

To prove that your values are correct, take any of the equations and replace their values.


y=4x-13\\3=4(4)-13\\3=16-13\\3=3

User Shang Wang
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.